Biogeochemical markers in juvenile Leach's storm-petrels (Hydrobates leucorhous) stranded offshore are distinct from inshore stranded juveniles and nestlings - Anne N.M.A. Ausems; Sophie Roy; Alexander L. Bond; Laura Crick; Joshua T. Cunningham; April Hedd; Laura A. McFarlane Tranquilla; Jennifer C. Rock; Robert A. Ronconi; Katharine R. Studholme; Christopher R.E. Ward; Sabina I. Wilhelm; et al. (Marine Pollution Bulletin, 2026)

Direct Versus Indirect Bypass in Early-Stage Moyamoya (Suzuki I-III): A Propensity Score-Weighted Study - Basel Musmar; Joanna M. Roy; Hammam Abdalrazeq; Victor Gabriel El-Hajj; Michael Rizzuto; Matthews Lan; Pious Patel; Michael Baldassari; Arbaz Momin; Yazan Shamli Oghli; Marissa Tucci; Joseph Schaefer; et al. (Translational Stroke Research, 2026)

Tracing a Decade of Tilapia Lake Virus Research: Breakthroughs, Challenges, and Projections - Dorothea V. Megarani; Christopher J. Martyniuk; Roy P. E. Yanong; Felipe Pierezan; Win Surachetpong; Kuttichantran Subramaniam (Reviews in Aquaculture, 2026)
Tilapia are one of the most farmed fish groups worldwide, with global production exceeding 6.55 million tons in 2022, generating an estimated market value of approximately USD 20.9 billion. Tilapia are favored for their fast growth rate, adaptability to various farming environments, and high nutritional value as a protein source. However, the tilapia industry has encountered a significant challenge with the emergence of tilapia lake virus (TiLV), first noted in 2014. This highly contagious virus has the potential to devastate tilapia populations, leading to substantial economic losses and raising serious concerns about food security in countries reliant on this fish for livelihoods and sustenance. The rapid spread of TiLV and its significant impact on the tilapia industry have led to widespread concerns among stakeholders, researchers, and policymakers. In response, there has been an increasing focus on research and development of effective strategies to control and manage TiLV infections. This review paper aims to provide a comprehensive overview of the substantial advancements in the understanding of TiLV, delving into its genetic variation and manipulation, molecular pathogenesis, epidemiology, transmission pathways, clinical signs, diagnosis, and the underlying pathogenesis of the virus. Additionally, we summarize the current knowledge on the potential impact of TiLV on the global tilapia industry and the measures being implemented to control its spread. Finally, we discuss ongoing scientific efforts toward the development of vaccines and other innovative strategies for effectively managing TiLV infections, highlighting the importance of continued research to secure the future of tilapia aquaculture on a global scale.

One‐Pot RT ‐ LAMP CRISPR /Cas12b Platform for Rapid Detection of Tilapia Lake Virus - Dorothea V. Megarani; Lilia Yang; Hannah J. Siler; Eva M. Quijano Cardé; Christopher J. Martyniuk; Paul M. Hick; Joy A. Becker; Esteban Soto; Win Surachetpong; Roy P. E. Yanong; Kuttichantran Subramaniam (Journal of Fish Diseases, 2026)
Tilapia Lake Virus (TiLV) is a significant threat to global tilapia aquaculture, highlighting the need for rapid and accurate diagnostic methods to manage outbreaks and minimise economic losses. This study presents the development and partial validation of a one‐pot assay integrating RT‐LAMP with the CRISPR/Cas12b system for sensitive and specific TiLV detection. This assay amplifies viral RNA using RT‐LAMP, while CRISPR/Cas12b enables a real‐time detectable signal. Targeting a conserved region in TiLV segment four, the assay achieves results within 75 min at 62°C, with easy visualisation using a portable fluorescence viewer. It demonstrated high sensitivity, with a 95% limit of detection of 79.6 copies (95% CI: 48–132 copies), and high specificity, with no cross‐reaction to other fish RNA or DNA viruses. Based on a validation panel of 261 samples from 9 source populations, the assay exhibited 92% diagnostic sensitivity (95% CI: 87%–96%) and 100% diagnostic specificity (95% CI: 97%–100%). When assessed as a non‐lethal sample, gills provided a reliable and less invasive alternative despite lower viral loads compared to internal organs. Therefore, this partially validated one‐pot assay is potentially practical for enhancing TiLV detection and disease management in aquaculture systems, especially in field settings and resource‐limited laboratories.

Effective science communication in the face of water crises: a community perspective on challenges and best practice in HELPING - Christina Orieschnig; Soham Adla; Kwok Pan Chun; Saumya Srivastava; Khosro Morovati; Ben C. Howard; Thanti Octavianti; José Gescilam Uchôa; Zheng Duan; Paola Mazzoglio; Anandharuban Panchanathan; Borbála Széles; et al. (Hydrological Sciences Journal, 2026)

Outcomes of Bypass Surgery in Patients with Moyamoya Syndrome Secondary To Sickle Cell Disease: a Multicenter Study - Basel Musmar; Joanna M. Roy; Hammam Abdalrazeq; Celine Yacoub; Nimer Adeeb; Antony A. Fuleihan; Sravanthi Koduri; Michael Baldassari; Matthews Lan; Pious Patel; Arbaz A. Momin; Elias Atallah; et al. (Translational Stroke Research, 2026)

deadtrees.earth — An open-access and interactive database for centimeter-scale aerial imagery to uncover global tree mortality dynamics - Clemens Mosig; Janusch Vajna-Jehle; Miguel D. Mahecha; Yan Cheng; Henrik Hartmann; David Montero; Samuli Junttila; Stéphanie Horion; Mirela Beloiu Schwenke; Michael J. Koontz; Khairul Nizam Abdul Maulud; Stephen Adu-Bredu; et al. (Remote Sensing of Environment, 2026)

Identifying individual drivers of damage to oak during severe UK storms in winter 2021 - Kate Halstead; Roy Sanderson; Salvatore Bonomo; Christopher Quine; Andrew Suggitt; Rachel Gaulton (Agricultural and Forest Meteorology, 2025)

The Harmonized Landsat and Sentinel-2 version 2.0 surface reflectance dataset - Junchang Ju; Qiang Zhou; Brian Freitag; David P. Roy; Hankui K. Zhang; Madhu Sridhar; John Mandel; Saeed Arab; Gail Schmidt; Christopher J. Crawford; Ferran Gascon; Peter A. Strobl; et al. (Remote Sensing of Environment, 2025)

Influence of urban layout on crime incidence using UAV images - Yusuf Bicer; Shouraseni Sen Roy; Richard Grant; Christopher Mader; Amin Sarafraz (Spatial Information Research, 2025)
Urban design and layout significantly influence crime patterns and community safety. Our study examines the effects of local-level urban layout on crime incidence in Coral Gables, a planned, higher-income area in Miami-Dade County, Florida. We assess key environmental attributes, including streetlights, layout, and sidewalks. Our analysis incorporates crime data, UAV orthophotos, and site-specific factors [e.g., streetlight illumination and sidewalk accessibility] to reveal spatiotemporal crime patterns. These patterns exhibit clustering and spatial unevenness. Neighborhood variability, including walkable, accessible neighborhoods, water barriers, gated community seclusion, and perimeter zones bordering lower-income and mixed-use development, influences crime distribution. The impact of streetlights varied across the city, with greater illumination, particularly from residential areas, acting as a significant deterrent against criminal activity. The northern area of Coral Gables aligns with higher crime concentration. Sidewalk accessibility affects crime rates, highlighting the importance of pedestrian-friendly infrastructure. Multi-residential buildings exhibit higher crime rates. Our findings underscore the significance of thoughtful urban planning and granular insights into micro-spatial patterns, which can inform targeted safety enhancements within specific neighborhood locations. Based on the current crime landscape in Coral Gables, we identify exciting avenues for future research with practical implications for crime prevention.

Environmental impact assessment of fish feed for aquaponic systems to introduce higher phosphorus and potassium in value-added fish sludge - Koushik Roy; Jaroslav Bernas; Radek Gebauer; Anil Axel Tellbuscher; Ondrej Nikl; Christopher Shaw; Ewumi Azeez Folorunso; Werner Kloas; Joel Aubin; Jan Mraz (Aquaculture, 2025)

The Contemporary Distribution of Scincine Lizards Does Not Reflect Their Biogeographic Origin - Aniruddha Datta‐Roy; Matthew C. Brandley; Christopher C. Austin; Aaron M. Bauer; David James Harris; Salvador Carranza; Kanishka D. B. Ukuwela; Anslem De Silva; Krystal A. Tolley; K. Praveen Karanth; Maitreya Sil (Journal of Biogeography, 2025)
Aim We assess the systematic relationships and historical biogeographic patterns in the subfamily Scincinae, a group of lizards that primarily inhabits the Afro‐Madagascan and Saharo‐Arabian regions with isolated lineages in Europe, North America, East Asia, India and Sri Lanka. The contemporary distribution of these lineages on the historical Laurasian and Gondwanan landmasses make scincines an ideal system to study the roles of vicariance and dispersal on a geologic scale of tens of millions of years. Location Global. Taxon Subfamily Scincinae (Family Scincidae). Methods We conducted biogeographic analyses on a reconstructed, time‐calibrated species tree of scincine genera, including members of the other Scincidae subfamilies, using seven nuclear loci (~6 k base pairs). We also constructed a lineage‐through‐time plot to assess the timing of diversification within scincines. Results Our analysis estimated strong support for the monophyly of Scincinae that is further comprised a strongly‐supported Gondwanan clade nested within a broader Laurasian group. While most of the extant, genus‐level diversity within the Gondwanan clade was accrued post‐Eocene, the majority of the Laurasian lineages diverged during the Palaeocene or earlier, suggesting large‐scale extinctions on continents of Laurasian origin. Counterintuitively, scincines from India and Sri Lanka have distinct biogeographical origins despite a long tectonic association between these landmasses, suggesting at least two independent, long‐distance, trans‐oceanic dispersal events into the subcontinent. Our biogeographic analyses suggest that scincines likely originated in East and Southeast Asia during the late Cretaceous ( ca . 70 Ma), and eventually dispersed westwards to Africa and Madagascar, where their greatest current‐day species richness occurs. Main Conclusions Our study demonstrates the concomitant roles of dispersal and extinction in shaping modern‐day assemblages of ancient clades such as scincine lizards. Our range evolution analysis shows that despite the greater diversity observed in the Afro‐Madagascan region, the origin of scincines can be traced back to Southeast Asia and East Asia, followed by westward dispersals. These dispersals may have been followed by significant extinctions in tropical East Asia, resulting in relatively lower diversity of scincines in these regions. Notably, our analysis reveals that Sri Lankan and Peninsular Indian scincines have distinct evolutionary origins.

Road salt chloride exposure in urban streambeds and links to groundwater – surface water interactions and salt sources - Grant Hodgins; Clare E. Robinson; Christopher Power; James W. Roy (Science of The Total Environment, 2024)

Towards better understanding the urban environment and its interactions with regional climate change - The WCRP CORDEX Flagship Pilot Study URB-RCC - Gaby S. Langendijk; Tomas Halenka; Peter Hoffmann; Marianna Adinolfi; Aitor Aldama Campino; Olivier Asselin; Sophie Bastin; Benjamin Bechtel; Michal Belda; Angelina Bushenkova; Angelo Campanale; Kwok Pan Chun; et al. (Urban Climate, 2024)

Localised damage patterns to oak during severe UK storms in winter 2021 - Kate Halstead; Rachel Gaulton; Roy Sanderson; Andrew Suggitt; Christopher Quine (Forest Ecology and Management, 2024)

Overcome imposter syndrome: Contribute to working groups and build strong networks - Amanda E. Bates; Megan A. Davies; Rick D. Stuart-Smith; Natali Lazzari; Jonathan S. Lefcheck; Scott D. Ling; Camille Mellin; David Mouillot; Anthony T.F. Bernard; Scott Bennett; Christopher J. Brown; Michael T. Burrows; et al. (Biological Conservation, 2024)

Animal versus plant protein sources in marine ingredient-free aquaponic diets: A case study on nutrient release, and retention of African catfish (Clarias gariepinus) reared in RAS - Christopher Shaw; Klaus Knopf; Koushik Roy; Christian Ulrichs; Werner Kloas (Aquaculture, 2024)

Aligning nature-based solutions with ecosystem services in the urban century - Roy P. Remme; Megan Meacham; Kara E. Pellowe; Erik Andersson; Anne D. Guerry; Benjamin Janke; Lingling Liu; Eric Lonsdorf; Meng Li; Yuanyuan Mao; Christopher Nootenboom; Tong Wu; et al. (Ecosystem Services, 2024)

Environmental plastics in the context of UV radiation, climate change, and the Montreal Protocol - Marcel A. K. Jansen; Anthony L. Andrady; Paul W. Barnes; Rosa Busquets; Laura E. Revell; Janet F. Bornman; Pieter J. Aucamp; Alkiviadis F. Bais; Anastazia T. Banaszak; Germar H. Bernhard; Laura S. Bruckman; Donat‐P. Häder; et al. (Global Change Biology, 2024)

Need and vision for global medium-resolution Landsat and Sentinel-2 data products - Volker C. Radeloff; David P. Roy; Michael A. Wulder; Martha Anderson; Bruce Cook; Christopher J. Crawford; Mark Friedl; Feng Gao; Noel Gorelick; Matthew Hansen; Sean Healey; Patrick Hostert; et al. (Remote Sensing of Environment, 2024)

Characterization of subsurface pathways contributing to freshwater salinization of urban streams using electrical and electromagnetic imaging techniques - Grant Hodgins; Clare E. Robinson; James W. Roy; Christopher Power (Science of The Total Environment, 2023)

Effects of Hudson River Stressors on Atlantic Tomcod: Contaminants and a Warming Environment - Isaac Wirgin; R. Christopher Chambers; John R. Waldman; Nirmal K. Roy; David A. Witting; Mark T. Mattson (Reviews in Fisheries Science & Aquaculture, 2023)

New insights on the origin of Barra volcanic ridge system, offshore Ireland: A long-distance influence of the Iceland mantle plume - Gaurav Tomar; Srikumar Roy; Christopher J. Bean; Satish C. Singh; Brian O'Reilly; Nick Schofield (Marine and Petroleum Geology, 2023)

Mechanisms underpinning community stability along a latitudinal gradient: Insights from a niche‐based approach - Luke Christopher Evans; Yolanda Melero; Reto Schmucki; Philipp H. Boersch‐Supan; Lluís Brotons; Colin Fontaine; Frédéric Jiguet; Mikko Kuussaari; Dario Massimino; Robert A. Robinson; David B. Roy; Oliver Schweiger; et al. (Global Change Biology, 2023)
At large scales, the mechanisms underpinning stability in natural communities may vary in importance due to changes in species composition, mean abundance, and species richness. Here we link species characteristics (niche positions) and community characteristics (richness and abundance) to evaluate the importance of stability mechanisms in 156 butterfly communities monitored across three European countries and spanning five bioclimatic regions. We construct niche‐based hierarchical structural Bayesian models to explain first differences in abundance, population stability, and species richness between the countries, and then explore how these factors impact community stability both directly and indirectly (via synchrony and population stability). Species richness was partially explained by the position of a site relative to the niches of the species pool, and species near the centre of their niche had higher average population stability. The differences in mean abundance, population stability, and species richness then influenced how much variation in community stability they explained across the countries. We found, using variance partitioning, that community stability in Finnish communities was most influenced by community abundance, whereas this aspect was unimportant in Spain with species synchrony explaining most variation; the UK was somewhat intermediate with both factors explaining variation. Across all countries, the diversity–stability relationship was indirect with species richness reducing synchrony which increased community stability, with no direct effects of species richness. Our results suggest that in natural communities, biogeographical variation observed in key drivers of stability, such as population abundance and species richness, leads to community stability being limited by different factors and that this can partially be explained due to the niche characteristics of the European butterfly assemblage.

Actinium and radium fluxes from the seabed in the northeast Pacific Basin - Nathaniel Kemnitz; Douglas E. Hammond; Paul Henderson; Emilie Le Roy; Matthew Charette; Willard Moore; Robert F. Anderson; Martin Q. Fleisher; Anne Leal; Erin Black; Christopher T. Hayes; Jess Adkins; et al. (Marine Chemistry, 2023)

Correction to: Clinical trial-ready patient cohorts for multiple system atrophy: coupling biospecimen and iPSC banking to longitudinal deep-phenotyping - Alain Ndayisaba; Ariana T. Pitaro; Ashlan S. Willett; Kristie A. Jones; Claudio Melo de Gusmao; Abby L. Olsen; Jisoo Kim; Eero Rissanen; Jared K. Woods; Sharan R. Srinivasan; Anna Nagy; Amanda Nagy; et al. (The Cerebellum, 2022)

Clinical Trial-Ready Patient Cohorts for Multiple System Atrophy: Coupling Biospecimen and iPSC Banking to Longitudinal Deep-Phenotyping - Alain Ndayisaba; Ariana T. Pitaro; Andrew S. Willett; Kristie A. Jones; Claudio Melo de Gusmao; Abby L. Olsen; Jisoo Kim; Eero Rissanen; Jared K. Woods; Sharan R. Srinivasan; Anna Nagy; Amanda Nagy; et al. (The Cerebellum, 2022)
Multiple system atrophy (MSA) is a fatal neurodegenerative disease of unknown etiology characterized by widespread aggregation of the protein alpha-synuclein in neurons and glia. Its orphan status, biological relationship to Parkinson’s disease (PD), and rapid progression have sparked interest in drug development. One significant obstacle to therapeutics is disease heterogeneity. Here, we share our process of developing a clinical trial-ready cohort of MSA patients (69 patients in 2 years) within an outpatient clinical setting, and recruiting 20 of these patients into a longitudinal “n-of-few” clinical trial paradigm. First, we deeply phenotype our patients with clinical scales (UMSARS, BARS, MoCA, NMSS, and UPSIT) and tests designed to establish early differential diagnosis (including volumetric MRI, FDG-PET, MIBG scan, polysomnography, genetic testing, autonomic function tests, skin biopsy) or disease activity (PBR06-TSPO). Second, we longitudinally collect biospecimens (blood, CSF, stool) and clinical, biometric, and imaging data to generate antecedent disease-progression scores. Third, in our Mass General Brigham SCiN study ( s tem c ells i n n eurodegeneration), we generate induced pluripotent stem cell (iPSC) models from our patients, matched to biospecimens, including postmortem brain. We present 38 iPSC lines derived from MSA patients and relevant disease controls (spinocerebellar ataxia and PD, including alpha-synuclein triplication cases), 22 matched to whole-genome sequenced postmortem brain. iPSC models may facilitate matching patients to appropriate therapies, particularly in heterogeneous diseases for which patient-specific biology may elude animal models. We anticipate that deeply phenotyped and genotyped patient cohorts matched to cellular models will increase the likelihood of success in clinical trials for MSA.

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Bioclimatic context of species' populations determines community stability - Luke Christopher Evans; Yolanda Melero; Reto Schmucki; Philipp H. Boersch‐Supan; Lluís Brotons; Colin Fontaine; Frédéric Jiguet; Mikko Kuussaari; Dario Massimino; Robert A. Robinson; David B. Roy; Oliver Schweiger; et al. (Global Ecology and Biogeography, 2022)
Aim It is important to understand the factors affecting community stability because ecosystem function is increasingly at risk from biodiversity loss. Here, we evaluate how a key factor, the position of local environmental conditions within the thermal range of the species, influences the stability of butterfly communities at a continental scale. Location Spain, UK and Finland. Time period 1999–2017. Major taxa studied Butterflies. Methods We tested the following hypotheses about how species responses to temperature anomalies aggregate to influence stability: Hypothesis 1, species have contrasting responses to local temperature anomalies at opposing edges of their thermal range; hypothesis 2, communities with central thermal range positions have higher community stability; and the impacts of thermal range position on community stability are driven by hypothesis 3, population asynchrony, or hypothesis 4, additive population stability. Data were analysed at 876 sites for 157 species. Results We found some support for hypothesis 1, because there were interactions between thermal range and response to temperature anomalies such that species at different range edges could provide weak compensatory dynamics. However, responses were nonlinear, suggesting strong declines with extreme anomalies, particularly at the hot range edge. Hypothesis 2 was supported in part, because community stability increased with central thermal range positions and declined at the edges, after accounting for species richness and community abundance. Thermal range position was weakly correlated with asynchrony (hypothesis 3) and population stability (hypothesis 4), although species richness and population abundance had larger impacts. Main conclusions Future extreme heat events will be likely to impact species negatively across their thermal range, but might be particularly impactful on populations at the hottest end of the thermal range. Thermal range position influenced community stability because range edge communities were stable. However, the prediction of community stability from thermal range position is challenging because of nonlinear responses to temperature, with small temperature anomalies producing weak compensatory dynamics, but large extreme events synchronizing dynamics.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

A Spatial Web Application to Explore the Interactions between Human Mobility, Government Policies, and COVID-19 Cases - Christopher Chapin; Shouraseni Sen Roy (Journal of Geovisualization and Spatial Analysis, 2021)

COVID-19 IgG/IgM antibody testing in Los Angeles County, California - Khadije Ahmad; Vahid Rezvanizadeh; Suraj Dahal; April Kinninger; Ahmed K. Ghanem; Suvasini Lakshmanan; Sajad Hamal; Ferdinand Flores; Christopher Dailing; Sion K. Roy; Matthew J. Budoff (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Exploring the Diversity of the Marine Environment for New Anti-cancer Compounds - Divya L. Dayanidhi; Beatrice C. Thomas; Joshua S. Osterberg; Mallissa Vuong; Giselle Vargas; Sarah K. Kwartler; Emma Schmaltz; Meagan M. Dunphy-Daly; Thomas F. Schultz; Daniel Rittschof; William C. Eward; Christopher Roy; et al. (Frontiers in Marine Science, 2021)
Marine ecosystems contain over 80% of the world’s biodiversity, and many of these organisms have evolved unique adaptations enabling survival in diverse and challenging environments. The biodiversity within the world’s oceans is a virtually untapped resource for the isolation and development of novel compounds, treatments, and solutions to combat human disease. In particular, while over half of our anti-cancer drugs are derived from natural sources, almost all of these are from terrestrial ecosystems. Yet, even from the limited analyses to date, a number of marine-derived anti-cancer compounds have been approved for clinical use, and several others are currently in clinical trials. Here, we review the current suite of marine-derived anti-cancer drugs, with a focus on how these compounds act upon the hallmarks of cancer. We highlight potential marine environments and species that could yield compounds with unique mechanisms. Continued exploration of marine environments, along with the characterization and screening of their inhabitants for unique bioactive chemicals, could prove fruitful in the hunt for novel anti-cancer therapies.

LC‐IMPACT: A regionalized life cycle damage assessment method - Francesca Verones; Stefanie Hellweg; Assumpció Antón; Ligia B. Azevedo; Abhishek Chaudhary; Nuno Cosme; Stefano Cucurachi; Laura de Baan; Yan Dong; Peter Fantke; Laura Golsteijn; Michael Hauschild; et al. (Journal of Industrial Ecology, 2020)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Special issue: Advances in convection-permitting climate modeling - Andreas F. Prein; Roy Rasmussen; Christopher L. Castro; Aiguo Dai; Justin Minder (Climate Dynamics, 2020)

Invasive non‐native species likely to threaten biodiversity and ecosystems in the Antarctic Peninsula region - Kevin A. Hughes; Oliver L. Pescott; Jodey Peyton; Tim Adriaens; Elizabeth J. Cottier‐Cook; Gillian Key; Wolfgang Rabitsch; Elena Tricarico; David K. A. Barnes; Naomi Baxter; Mark Belchier; Denise Blake; et al. (Global Change Biology, 2020)
The Antarctic is considered to be a pristine environment relative to other regions of the Earth, but it is increasingly vulnerable to invasions by marine, freshwater and terrestrial non‐native species. The Antarctic Peninsula region (APR), which encompasses the Antarctic Peninsula, South Shetland Islands and South Orkney Islands, is by far the most invaded part of the Antarctica continent. The risk of introduction of invasive non‐native species to the APR is likely to increase with predicted increases in the intensity, diversity and distribution of human activities. Parties that are signatories to the Antarctic Treaty have called for regional assessments of non‐native species risk. In response, taxonomic and Antarctic experts undertook a horizon scanning exercise using expert opinion and consensus approaches to identify the species that are likely to present the highest risk to biodiversity and ecosystems within the APR over the next 10 years. One hundred and three species, currently absent in the APR, were identified as relevant for review, with 13 species identified as presenting a high risk of invading the APR. Marine invertebrates dominated the list of highest risk species, with flowering plants and terrestrial invertebrates also represented; however, vertebrate species were thought unlikely to establish in the APR within the 10 year timeframe. We recommend (a) the further development and application of biosecurity measures by all stakeholders active in the APR, including surveillance for species such as those identified during this horizon scanning exercise, and (b) use of this methodology across the other regions of Antarctica. Without the application of appropriate biosecurity measures, rates of introductions and invasions within the APR are likely to increase, resulting in negative consequences for the biodiversity of the whole continent, as introduced species establish and spread further due to climate change and increasing human activity.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Taxonomy of the order Bunyavirales: update 2019 - Abulikemu Abudurexiti; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Tatjana Avšič-Županc; Matthew J. Ballinger; Dennis A. Bente; Martin Beer; Éric Bergeron; Carol D. Blair; Thomas Briese; Michael J. Buchmeier; et al. (Archives of Virology, 2019)

Taxonomy of the order Bunyavirales: second update 2018 - Piet Maes; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; Matthew J. Ballinger; Dennis A. Bente; Martin Beer; Éric Bergeron; Carol D. Blair; Thomas Briese; Michael J. Buchmeier; Felicity J. Burt; et al. (Archives of Virology, 2019)

3D Cosmic Ray Muon Tomography from an Underground Tunnel - Elena Guardincerri; Charlotte Rowe; Emily Schultz-Fellenz; Mousumi Roy; Nicolas George; Christopher Morris; Jeffrey Bacon; Matthew Durham; Deborah Morley; Kenie Plaud-Ramos; Daniel Poulson; Diane Baker; et al. (Pure and Applied Geophysics, 2017)

Metastatic liver tumour segmentation with a neural network-guided 3D deformable model - Eugene Vorontsov; An Tang; David Roy; Christopher J. Pal; Samuel Kadoury (Medical & Biological Engineering & Computing, 2017)

A cost–benefit model for plant–plant interactions: a density-series tool to detect facilitation - Christopher J. Lortie; Alessandro Filazzola; Clive Welham; Roy Turkington (Plant Ecology, 2016)

Direct Writing of Polymeric Coatings on Magnesium Alloy for Tracheal Stent Applications - Jessica Perkins; Zhigang Xu; Christopher Smith; Abhijit Roy; Prashant N. Kumta; Jenora Waterman; Dawn Conklin; Salil Desai (Annals of Biomedical Engineering, 2015)

siRNA-Mediated Knockdown of P450 Oxidoreductase in Rats: A Tool to Reduce Metabolism by CYPs and Increase Exposure of High Clearance Compounds - Rob S. Burke; Inthirai Somasuntharam; Paul Rearden; Duncan Brown; Sujal V. Deshmukh; Martha A. DiPietro; Jillian DiMuzio; Roy Eisenhandler; Scott E. Fauty; Christopher Gibson; Marian E. Gindy; Kelly A. Hamilton; et al. (Pharmaceutical Research, 2014)

Ecological correlates of local extinction and colonisation in the British ladybird beetles (Coleoptera: Coccinellidae) - Richard F. Comont; Helen E. Roy; Richard Harrington; Christopher R. Shortall; Bethan V. Purse (Biological Invasions, 2014)

Can trait‐based analyses of changes in species distribution be transferred to new geographic areas? - Gary D. Powney; Christopher D. Preston; Andy Purvis; Wouter Van Landuyt; David B. Roy (Global Ecology and Biogeography, 2014)
Aim Anthropogenic environmental change is having a major impact on biodiversity. By identifying traits that correlate with changes in species range, comparative studies can shed light on the mechanisms driving this change; but such studies will be more useful for conservation if they have true predictive power, i.e. if their trait‐based models can be transferred to new regions. We aim to examine the ability of trait‐based models to predict changes in plant distribution across seven geographic regions that varied in terms of land cover and species composition. Location B ritain and F landers ( B elgium). Methods We estimated distribution change for more than 1000 species for over 70 years of data (1930s to 2004), using data from published plant atlases. We identified regional trait‐based models of plant distribution change. Traits included morphological characteristics, E llenberg values and distribution‐based traits. The trait models were then used to predict change in all other regions, with the level of linear correlation between predicted and observed changes in range used as a measure of transferability. We then related transferability to land cover and species similarity between regions. Results We found that trait correlates of range change varied regionally, highlighting the regional variation in the drivers of range change in plants. These trait models also varied in the amount of variation explained, with r 2 values ranging from 0.05 to 0.17. A key cross‐regional difference was the variation in the relationship between soil nutrient association ( E llenberg N ) and distribution change, which was strongly positive in F landers and southern E ngland but significantly negative in northern Scotland. We found that transferability between regions was significantly correlated with the level of similarity in land cover. Main conclusions We conclude that trait‐based models can predict broad‐scale changes in species distributions in regions that share similar land‐cover composition; however, predictions between regions with differing land‐cover cover tend to be poor.

A phylogenetically-informed trait-based analysis of range change in the vascular plant flora of Britain - Gary D. Powney; Giovanni Rapacciuolo; Christopher D. Preston; Andy Purvis; David B. Roy (Biodiversity and Conservation, 2014)

Genetic epidemiology of cardiometabolic risk factors and their clustering patterns in Mexican American children and adolescents: the SAFARI Study - Sharon P. Fowler; Sobha Puppala; Rector Arya; Geetha Chittoor; Vidya S. Farook; Jennifer Schneider; Roy G. Resendez; Ram Prasad Upadhayay; Jane VandeBerg; Kelly J. Hunt; Benjamin Bradshaw; Eugenio Cersosimo; et al. (Human Genetics, 2013)

MRI volume of the medial frontal cortex predicts financial capacity in patients with mild Alzheimer’s disease - Luke E. Stoeckel; Christopher C. Stewart; H. Randall Griffith; Kristen Triebel; Ozioma C. Okonkwo; Jan A. den Hollander; Roy C. Martin; Katherine Belue; Jacquelynn N. Copeland; Lindy E. Harrell; John C. Brockington; David G. Clark; et al. (Brain Imaging and Behavior, 2013)

Taxon‐ and vector‐specific variation in species richness and abundance during the transport stage of biological invasions - Elizabeta Briski; Sarah A. Bailey; Oscar Casas-Monroy; Claudio DiBacco; Irena Kaczmarska; Janice E. Lawrence; Jonas Leichsenring; Colin Levings; Michael L. MacGillivary; Christopher W. McKindsey; Leslie E. Nasmith; Marie Parenteau; et al. (Limnology and Oceanography, 2013)
Recent empirical and statistical evidence suggest that propagule pressure (i.e., number of individuals introduced per event, and the number and frequency of events) and colonization pressure (i.e., number of species released per event, and the number and frequency of events) are of vital importance to invasion success. To explore possible changes in propagule and colonization pressure during the transport stage of the invasion process, we examine abundance and species richness of virus‐like particles, bacteria, diatoms, dinoflagellates, and invertebrates transported in commercial ships—a leading vector for global spread of aquatic nonindigenous species. We collected 154 ballast water samples from ships that had performed or were exempt from ballast water exchange (BWE) prior to arrival at Pacific and Atlantic ports in Canada and Laurentian Great Lakes ports. We found that abundance and species richness varied across taxa and regions, with ships arriving to the Atlantic region carrying the highest abundance of taxa. The highest species richness of invertebrates and diatoms was recorded from ships arriving to the Pacific, whereas the richest communities of dinoflagellates occurred in the Atlantic region. We also found that BWE had no effect on abundance or species richness of most taxa (dinoflagellates, diatoms, bacteria, and virus‐like particles), whereas the effect on abundance of invertebrates was not clear. Finally, longer voyages resulted in lower abundance of all taxa except dinoflagellates, and lower species richness of diatoms. Paradoxically, the elevated abundance and species richness of dinoflagellates following BWE suggest that this group could have enhanced invasion potential when ships manage ballast water by exchange.

The Evolutionary Histories of Clinical and Environmental SHV β-Lactamases are Intertwined - Robert L. Dorit; Christopher M. Roy; Sandra M. Robinson; Margaret A. Riley (Journal of Molecular Evolution, 2013)

Using biological traits to explain ladybird distribution patterns - Richard F. Comont; Helen E. Roy; Owen T. Lewis; Richard Harrington; Christopher R. Shortall; Bethan V. Purse (Journal of Biogeography, 2012)
Aim Determining to what extent differing distribution patterns are governed by species’ life‐history and resource‐use traits may lead to an improved understanding of the impacts of environmental change on biodiversity. We investigated the extent to which traits can explain distribution patterns in the ladybird fauna (Coleoptera: Coccinellidae) of Great Britain. Location The British mainland and inshore islands (Anglesey, the Isle of Wight and the Inner Hebrides). Methods The distributions of 26 ladybird species resident in Britain were characterized in terms of their range size (from 2661 10‐km grid squares across Britain) and proportional range fill (at 10‐ and 50‐km scales). These were assessed relative to five traits (body length, elytral colour pattern polymorphism, voltinism, habitat specificity and diet breadth). The role of phylogenetic autocorrelation was examined by comparing the results of phylogenetic and generalized least‐squares regressions. Results Diet breadth was the only trait correlated with range size: species with broad diets had larger range sizes than dietary specialists. Range fill was sensitive to recording intensity (a per‐species measure of the mean number of records across occupied squares); models including both recording intensity and range size provided more explanatory power than models incorporating ecological traits alone. Main conclusions Habitat specificity is often invoked to explain the distribution patterns of species, but here we found diet breadth to be the only ecological correlate of both range fill and range size. This highlights the importance of understanding predator–prey interactions when attempting to explain the distribution patterns of predatory species. Our results suggest that the diet breadth of predatory species is a better correlate of range size and fill than other measures, such as habitat specificity.

Does phylogeny matter? Assessing the impact of phylogenetic information in ecological meta‐analysis - Scott A. Chamberlain; Stephen M. Hovick; Christopher J. Dibble; Nick L. Rasmussen; Benjamin G. Van Allen; Brian S. Maitner; Jeffrey R. Ahern; Lukas P. Bell‐Dereske; Christopher L. Roy; Maria Meza‐Lopez; Juli Carrillo; Evan Siemann; et al. (Ecology Letters, 2012)
Meta‐analysis is increasingly used in ecology and evolutionary biology. Yet, in these fields this technique has an important limitation: phylogenetic non‐independence exists among taxa, violating the statistical assumptions underlying traditional meta‐analytic models. Recently, meta‐analytical techniques incorporating phylogenetic information have been developed to address this issue. However, no syntheses have evaluated how often including phylogenetic information changes meta‐analytic results. To address this gap, we built phylogenies for and re‐analysed 30 published meta‐analyses, comparing results for traditional vs. phylogenetic approaches and assessing which characteristics of phylogenies best explained changes in meta‐analytic results and relative model fit. Accounting for phylogeny significantly changed estimates of the overall pooled effect size in 47% of datasets for fixed‐effects analyses and 7% of datasets for random‐effects analyses. Accounting for phylogeny also changed whether those effect sizes were significantly different from zero in 23 and 40% of our datasets (for fixed‐ and random‐effects models, respectively). Across datasets, decreases in pooled effect size magnitudes after incorporating phylogenetic information were associated with larger phylogenies and those with stronger phylogenetic signal. We conclude that incorporating phylogenetic information in ecological meta‐analyses is important, and we provide practical recommendations for doing so.

A complete dynamical ozone budget measured in the tropical marine boundary layer during PASE - Stephen A. Conley; Ian C. Faloona; Donald H. Lenschow; Teresa Campos; Clifford Heizer; Andrew Weinheimer; Christopher A. Cantrell; Roy L. Mauldin; Rebecca S. Hornbrook; Ilana Pollack; Alan Bandy (Journal of Atmospheric Chemistry, 2011)

A nuclease-resistant RNA aptamer specifically inhibits angiopoietin-1-mediated Tie2 activation and function - Rebekah R. White; Julie A. Roy; Kristi D. Viles; Bruce A. Sullenger; Christopher D. Kontos (Angiogenesis, 2008)

Impediments and Solutions to Sustainable, Watershed-Scale Urban Stormwater Management: Lessons from Australia and the United States - Allison H. Roy; Seth J. Wenger; Tim D. Fletcher; Christopher J. Walsh; Anthony R. Ladson; William D. Shuster; Hale W. Thurston; Rebekah R. Brown (Environmental Management, 2008)

Linkage and association analysis of candidate genes for TB and TNFα cytokine expression: evidence for association with IFNGR1, IL-10, and TNF receptor 1 genes - Catherine M. Stein; Sarah Zalwango; Allan B. Chiunda; Christopher Millard; Dmitry V. Leontiev; Amanda L. Horvath; Kevin C. Cartier; Keith Chervenak; W. Henry Boom; Robert C. Elston; Roy D. Mugerwa; Christopher C. Whalen; et al. (Human Genetics, 2007)

Polyhydroxyalkanoates in Gram-positive bacteria: insights from the genera Bacillus and Streptomyces - Sabeel P. Valappil; Aldo R. Boccaccini; Christopher Bucke; Ipsita Roy (Antonie van Leeuwenhoek, 2006)

EphB3 receptor and ligand expression in the adult rat brain - Christopher A. Willson; Roy D. Foster; Stephen M. Onifer; Scott R. Whittemore; Jorge D. Miranda (Journal of Molecular Histology, 2006)

Climate factors influencing bacterial count in background air samples - Roy M. Harrison; Alan M. Jones; Peter D. E. Biggins; Nigel Pomeroy; Christopher S. Cox; Stephen P. Kidd; Jon L. Hobman; Nigel L. Brown; Alan Beswick (International Journal of Biometeorology, 2005)

Seasonal succession in fishless ponds: effects of enrichment and invertebrate predators on zooplankton community structure - Christopher F. Steiner; Allison H. Roy (Hydrobiologia, 2003)

Epidemiology of communicable disease in small populations - Christopher J. Rhodes; A. R. Butler; Roy M. Anderson (Journal of Molecular Medicine, 1998)

Cell cycle changes in A-type lamin associations detected in human dermal fibroblasts using monoclonal antibodies - Joanne A. Dyer; Ian R. Kill; Gareth Pugh; Roy A. Quinlan; E. Birgitte Lane; Christopher J. Hutchison (Chromosome Research, 1997)